Facile fabrication of an underwater superoleophobic mesh for effective separation of oil/simulated seawater mixtures. Issue 81 (16th August 2016) - Li, Dianming; Wu, Runni; Li, Jian; Li, Weijun; Zhang, Yan; She, Houde
Abstract : The underwater superoleophobic meshes can efficiently separate oil/simulated seawater mixture and exhibit excellent environmental stability. Abstract : Recently, oil/water separation has become a global challenge due to frequent oil spills. Herein, we demonstrate an underwater superoleophobic Ag coated mesh, which is fabricated by a facile galvanic exchange reaction. The mesh was used to study gravity-driven oil/simulated seawater separation, in which a separation efficiency of above 94.0% could be achieved. In addition, the Ag coated mesh can maintain this high separation efficiency after 45 separation cycles. Furthermore, the Ag coated mesh exhibits excellent environmental stability under harsh conditions. We believe that the Ag coated mesh can be applied for the development of functional materials for oil/water separation.